AAPS Open - Su, Yongchao; Riley, Christopher M.; Su, Yongchao; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
AAPS Open, the flagship open access journal of the American Association of Pharmaceutical Scientists, provides a global forum for the rapid publication of original research and discussion that demonstrates innovations and applications of scientific concepts and techniques across the breadth of the pharmaceutical sciences. Fully peer-reviewed, AAPS Open welcomes reports from experimental or theoretical studies during the entire course of drug development, for both small and large molecule drugs as well as other new therapeutic modalities including vaccines, cell and gene therapeutics, and nucleotide-based therapeutics. The journal$1 (Bs interests include - but are not limited to - drug discovery, translational research, preclinical studies, preformulation studies, drug product design, formulation and process development, analytical development, stability studies, biopharmaceutics and pharmacokinetic studies, drug delivery technologies, mechanistic studies, modeling and simulation, compendial and regulatory science, and post-launch commercial manufacturing. AAPS Open specifically welcomes white papers, commentaries, and perspectives from experts in their field, as well as meeting reports, and review articles. For reports of primary research, a high degree of innovation is required.s
Keywords: Pharmaceutical chemistry; Pharmacology; Pharmaceutics; Pharmacology